Knowledge, awareness and attitude of first aid among health sciences university students - Jamaludin, Thandar Soe Sumaiyah; Zakaria, Muhammad Allif; Saidi, Sanisah; Chong, Mei Chan (IIUM Press, 2018)
Objective: As the incidence of emergencies has steadily increased in recent years, it is important to ensure that individuals, including university students, are adequately trained to deal with such events. This study aimed to assess the level of knowledge and awareness of, and attitudes towards, first aid among IIUM Kuantan campus students. Method: A quantitative cross-sectional survey with stratified random sampling study was conducted among 348 students at the International Islamic University Malaysia (IIUM) Kuantan. Data were collected using a self-administered questionnaire which was adapted from Hong Kong Red Cross. The questionnaire was available in both English and the Malay language. Results: A total of 42.8% participants had a moderate level of first aid knowledge. However, 90.8% participants had awareness of and a positive attitude towards first aid knowledge. On the other hand, 55.4% of study participants had not experienced taking first aid courses and they had little knowledge of this. There were significant associations between gender, Kulliyyah or faculty, year of study, and first aid training experience, and the level of first aid knowledge based on a one-way ANOVA test with p-values of < 0.05 representing statistical significance. Conclusion: The findings indicate that most health sciences university students have good awareness and attitudes towards first aid. Nevertheless, implementation of regular educational programs with structured modules may be able to improve their knowledge of first aid practices and skills.